2013
DOI: 10.1007/s10639-012-9246-4
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use of Twitter by students for lecture engagement and discussion

Abstract: Research indicates that student engagement with lectures, and participation in discussion and debate, greatly improve their learning and experience of University. The nature of some lectures means they can lack opportunities for interaction and active learning. For this reason it can be difficult for some students, especially students new to University, to fully engage in lectures, and interact with their peers. This study attempts to use Twitter as a means of increasing these opportunities for interaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…However, one student did note that he preferred speaking aloud in class. This difference in preferred interaction styles reflects findings by Tiernan (2014), who described some students using Twitter to interact with the professor during a lecture, while other students asked questions aloud, in a more typical form of interaction. This indicates both forms of interaction may be important and providing a range of modes for students to share their ideas with their classmates and professors may be important in allowing the widest range of students to voice their opinions and receive support.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, one student did note that he preferred speaking aloud in class. This difference in preferred interaction styles reflects findings by Tiernan (2014), who described some students using Twitter to interact with the professor during a lecture, while other students asked questions aloud, in a more typical form of interaction. This indicates both forms of interaction may be important and providing a range of modes for students to share their ideas with their classmates and professors may be important in allowing the widest range of students to voice their opinions and receive support.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, Twitter chats -meetings or discussions held on Twitter -allow account holders to participate in conversations with experts or peers with related interests. The potential of these features, which have been used extensively for business and social purposes, have been recognised within education, with increasing examples of their use in a range of settings (e.g., Ally, 2012;Dhir et al, 2013;Gao et al, 2012;Junco et al, 2013;Markham and Belkasim, 2011;Tiernan, 2014). Dhir et al's (2013) review of Twitter as a learning tool, provides ten potential benefits for using this tool in education settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emily Purser, Angela Towndrow, and Ary Aranguiz (2013) have explored the relationship between peer tutoring and options for interacting in MOOCs through on-line learning-support tools, such as the hashtags used in #edcmooc. Peter Tiernan (2012) has also examined the role of Twitter in increasing interaction by students in academic conversations. His study concluded that Twitter has great potential for encouraging the development of virtual conversations outside the university once face-to-face classes have ended.…”
Section: Twitter Microblogging and Moocsmentioning
confidence: 99%
“…Student engagement is defined as the time and effort students invest in educational activities which are linked to desired outcomes (Kuh, 2009). It was observed that students have poorly adopted the tool, reporting that there were technological barriers and lack of motivation (Tiernan, 2013). Students reported that Twitter helps their interaction in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%